Pengaturan Kewenangan Pengelolaan dan Pengamanan Wilayah Maritim Negara - Supryadi, Ady; Aminwara, Rena (Yayasan Pendidikan Kardin Assidiq, 2025)
Background: Indonesia's strategic position as the world's maritime axis underscores its identity as an archipelagic and maritime nation, serving as a central point in the global supply chain. This positioning, however, exposes Indonesia to various threats and disruptions that can impact maritime security. In response, the government has tried to address these challenges by formulating legal frameworks to enhance the country's maritime security. Despite the development of numerous regulations applicable at sea, these laws remain largely sectoral, resulting in disharmony and overlapping authorities within maritime security. Objective: This study aims to analyze the inconsistencies and overlaps in regulations and authorities governing Indonesia's maritime security due to the existence of sectoral legal products. Additionally, it recommends a comprehensive legal framework to facilitate effective maritime law enforcement. Method: The research employs normative legal research methodologies, utilising legislative and conceptual approaches, with data analysis conducted through descriptive qualitative methods. Results: The current regulatory authority for managing and securing Indonesia's maritime territory remains fragmented, leading to overlaps in implementation. Conclusion and Recommendation: The primary recommendation is for the government, in collaboration with the DPR, to promptly harmonize existing laws and regulations related to maritime affairs. Moreover, the mechanisms for law enforcement should be clearly and firmly established within these regulations to promote order and efficacy in maritime law enforcement.